The Effect of the Phonics Method on the Development of English Reading and Speaking Abilities in Children Aged 4–5 Years - Noventy, Elisabeth Susi; Fitri, Ruqoyyah; Setyowati, Sri; Lasarus, Matheos (IKIP Widya Darma Surabaya, 2026)
Objective: This study aims to examine the influence of the phonics method on the development of English reading and speaking abilities in children aged 4–5 years at Happy Kids Kindergarten. Method: This study employed a quantitative approach using a quasi-experimental pretest–posttest control group design. The participants consisted of 20 children, divided into a control group (n = 10) and an experimental group (n = 10). Data were collected using a structured observation checklist that measured eight indicators of reading and speaking abilities. The data were analyzed using descriptive statistics and an independent samples t-test. Results: The results showed that the experimental group achieved a mean score of 27.5 (85.9%), which was categorized as “Developing as Expected” (BSH), higher than that of the control group, which obtained a mean score of 20.4 (63.75%) in the category of